Landscape Genomics Provides Evidence of Ecotypic Adaptation and a Barrier to Gene Flow at Treeline for the Arctic Foundation Species Eriophorum vaginatum - Stunz, Elizabeth; Fetcher, Ned; Lavretsky, Philip; Mohl, Jonathon E.; Tang, Jianwu; Moody, Michael L. (Frontiers in Plant Science, 2022)
Global climate change has resulted in geographic range shifts of flora and fauna at a global scale. Extreme environments, like the Arctic, are seeing some of the most pronounced changes. This region covers 14% of the Earth’s land area, and while many arctic species are widespread, understanding ecotypic variation at the genomic level will be important for elucidating how range shifts will affect ecological processes. Tussock cottongrass (Eriophorum vaginatum L.) is a foundation species of the moist acidic tundra, whose potential decline due to competition from shrubs may affect ecosystem stability in the Arctic. We used double-digest Restriction Site-Associated DNA sequencing to identify genomic variation in 273 individuals of E. vaginatum from 17 sites along a latitudinal gradient in north central Alaska. These sites have been part of 30+ years of ecological research and are inclusive of a region that was part of the Beringian refugium. The data analyses included genomic population structure, demographic models, and genotype by environment association. Genome-wide SNP investigation revealed environmentally-associated variation and population structure across the sampled range of E. vaginatum, including a genetic break between populations north and south of treeline. This structure is likely the result of subrefugial isolation, contemporary isolation by resistance, and adaptation. Forty-five candidate loci were identified with genotype-environment association analyses, with most identified genes related to abiotic stress. Our results support a hypothesis of limited gene flow based on spatial and environmental factors for E. vaginatum, which in combination with life history traits could limit range expansion of southern ecotypes northward as the tundra warms. This has implications for lower competitive attributes of northern plants of this foundation species likely resulting in changes in ecosystem productivity.